Composite solutions with recycled textile wastes. Issue 1 (1st February 2022) - Todor, M P; Rackov, M; Kiss, I; Cioata, V G
Abstract: Textile waste amounts represent a remarkable issue whether they are produced during production and processing of textile materials, such as production waste and excesses (industrial or pre-consumption), or at the end-of-life of products, once it had been sold and used (post-consumer materials). Whereas pre-consumer textiles can be easier recycled because we know their general composition and sources, post-consumer textiles often consist of different materials that need to be taken apart to be regenerated. Valuable resources held within the waste are also lost. Having in view that 50% of collected clothing is re-wearable, and the rest could be recycled, a particular attention have to be given to recycling processes for both products and waste, aiming at reintroducing them in a new industrial process, through new manufacturing ways, and so, starting a new life-cycle. The textile reuse and recycling, in general, reduce environmental impact compared to incineration and landfilling. There are different approaches to be used and different ways to identify suitable technologies that could lead product manufacturing towards a remarkable reduction of production costs, while considering recyclable materials as a real and efficient alternative. Among them, there are technologies for waste recovery, which transforms textile waste into secondary raw materials, creating circularity and reducing environmental impact. Studies have shown that different textile waste can be used in composite solutions. This type of reinforcements has become a major research subject in recent years. This study aims to investigate the composite solutions with recycled textile waste.